Prediction of by-Products from Wet Air Oxidation Module for Sludge Treatment of Produced Water - bi Cho, Eun; hyung Kang, Choon; ju Hwang, In (International Journal of Engineering and Technology, 2018)
This study presents and verifies the deep-well wet air oxidation (WAO) reaction model for treating organic sludge (among the various by-products discharged from produced water treatment facilities) for recycling, and predicts the reaction characteristics. The deep-well WAO reaction model is established theoretically and a simulation model is developed. The validity of the simulation model is examined by comparing the modeled pressure change inside the reactor with that given by a model developed in a previous study. In terms of the pressure profile inside the reactor, the developed simulation model shows a 2.3% difference from the previously proposed model. It is confirmed that the increase in reaction pressure and residence time inside the deep-well WAO reactor improves organic decomposition by increasing the oxygen mass transfer rate in water containing such organics.Â Â